EVALUASI MODEL CIPP PADA PROGRAM LITERASI SEKOLAH DI SMP - Ponto, Herlin Pebrianti Yuanita; Rasyid, Muhammad Nur Akbar; Mania, Sitti (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2025)
This study aims to evaluate the implementation of the literacy program at SMP Negeri 2 Parigi using the CIPP Model (Context, Input, Process, Product). This model was chosen for its ability to comprehensively evaluate programs, from the context of program needs, the resources used, the implementation process, to the outcomes achieved. Data were collected through interviews, observations, and documentation involving the school principal, teachers, students, and librarian. Data analysis was conducted qualitatively with triangulation techniques to ensure data validity. The results show that the literacy program at SMP Negeri 2 Parigi is a strategic initiative to enhance students' literacy culture. Context evaluation revealed that the program was designed to address students' low reading interest and improve literacy skills, although integration of literacy into all subjects is still needed. In terms of input, human resources and facilities are available but remain limited, particularly in the collection of books and budget allocation. Process evaluation indicated that the program runs regularly every week with an average participation rate of 75%. However, consistency in implementation and the engagement of students with low literacy skills need improvement. Product evaluation showed significant improvements in reading interest and literacy skills, with 50% of students reaching the "good" category after one semester, although the results are not yet evenly distributed across all student groups. Strategic recommendations include increasing book collections, providing teacher training, supporting students with low literacy skills, and strengthening the monitoring and evaluation system. With appropriate modifications, the program is deemed feasible to continue, offering a more significant impact on the school's literacy culture. ABSTRAKPenelitian ini bertujuan untuk mengevaluasi pelaksanaan program literasi di SMP Negeri 2 Parigi menggunakan Model CIPP (Context, Input, Process, Product). Model ini digunakan karena kemampuannya mengevaluasi program secara menyeluruh, mulai dari konteks kebutuhan program, masukan yang digunakan, proses pelaksanaan, hingga hasil yang dicapai. Data dikumpulkan melalui wawancara, observasi, dan dokumentasi dari kepala sekolah, guru, siswa, dan pustakawan. Analisis data dilakukan secara kualitatif dengan teknik triangulasi untuk memastikan keabsahan data. Hasil penelitian menunjukkan bahwa program literasi di SMP Negeri 2 Parigi merupakan inisiatif strategis untuk meningkatkan budaya literasi siswa. Evaluasi konteks mengungkapkan bahwa program dirancang untuk mengatasi rendahnya minat baca siswa dan meningkatkan kemampuan literasi, meskipun diperlukan integrasi literasi ke seluruh mata pelajaran. Pada aspek input, sumber daya manusia dan fasilitas tersedia tetapi masih terbatas, terutama dalam koleksi buku dan alokasi anggaran. Evaluasi proses menunjukkan bahwa program berjalan secara rutin setiap pekan dengan partisipasi rata-rata 75%, namun konsistensi pelaksanaan dan keterlibatan siswa dengan kemampuan literasi rendah masih perlu ditingkatkan. Evaluasi produk menunjukkan peningkatan signifikan pada minat baca dan kemampuan membaca siswa, dengan 50% siswa mencapai kategori "baik" setelah program berjalan selama satu semester, meskipun hasil ini belum merata di semua kelompok siswa. Rekomendasi strategis meliputi peningkatan koleksi buku, pelatihan guru, dukungan bagi siswa dengan kemampuan rendah, serta penguatan sistem monitoring dan evaluasi. Dengan modifikasi yang sesuai, program ini dinilai layak untuk dilanjutkan guna memberikan dampak yang lebih signifikan terhadap budaya literasi di sekolah.